New species of quill mites (Acari, Cheyletoidea, Syringophilidae) and the first record of male for the genus Stibarokris - Glowska, Eliza; Skoracki, Maciej (Zootaxa, 2011)
In this paper we describe a new quill mite species Stibarokris dastychi sp. nov., parasitizing Great Cormorant Phalacrocorax carbo (Linnaeus) (Pelecaniformes: Phalacrocoracidae) and the male of S. phoeniconaias Skoracki et OConnor, 2010 from American Flamingo Phoenicopterus ruber Linnaeus (new host). Additionally, the improved (including both female and male) diagnosis of the genus Stibarokris Kethley, 1970 and the key to all known species of this genus are given.